2008
DOI: 10.1007/s12325-008-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and tolerability of epoetin zeta, administered intravenously, for maintenance treatment of renal anemia

Abstract: The evaluation of the primary endpoints provided data supporting the intravenous administration of epoetin zeta in patients with chronic renal failure. Neutralizing antibodies against erythropoietin were not detected, and there were no reports of patients with increasing erythropoietin resistance. Our results suggest that intravenous administration of epoetin zeta is effective regarding its ability to maintain stabilized hemoglobin levels within the target range of 10.5-12.5 g/dL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
(28 reference statements)
1
24
0
Order By: Relevance
“…SB309 maintained target Hb levels with a constant dose. Approximately 5% of the adverse events were considered to be related to the study treatment, and they were consistent with those previously reported with all ESAs (30). In a post hoc analysis of the three studies above comparing SB309 with epoetin alfa, the incidence of adverse events was not significantly different between the two treatments (31).…”
Section: Sb309 (Retacrit)supporting
confidence: 84%
“…SB309 maintained target Hb levels with a constant dose. Approximately 5% of the adverse events were considered to be related to the study treatment, and they were consistent with those previously reported with all ESAs (30). In a post hoc analysis of the three studies above comparing SB309 with epoetin alfa, the incidence of adverse events was not significantly different between the two treatments (31).…”
Section: Sb309 (Retacrit)supporting
confidence: 84%
“…As an example, there is evidence from the literature that epoetin zeta, administered intravenously, is therapeutically equivalent to epoetin alpha in the correction of low hemoglobin concentration in patients with CKD undergoing hemodialysis. [9,10] Binocrit Ò is not approved for subcutaneous (only for intravenous) administration in CKD and this factor may in theory discourage the use of this biosimilar in CKD patients because of increased discomfort for the patient. As a similarly low number of Retacrit Ò users with CKD was documented, a general skepticism of clinicians in using biosimilars rather than patients' discomfort may account for the low penetration of biosimilars in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…10 Comparable efficacy and safety between the SB309 and Eprex Âź was demonstrated in two randomized, doubleblind phase III clinical trials with intravenous administration, a correction phase and a maintenance phase study, involving 922 hemodialysis patients with renal anemia. 11,12 An additional maintenance treatment follow-up study was performed to obtain long-term safety data. 13 For both epoetins, there have been no reports of immunogenicity with the intravenous use of the drug.…”
Section: Appropriateness Of Use Of Biosimilar Epoetins In Practicementioning
confidence: 99%